Anterior Resection for Rectal Cancer and Visceral Blood Flow: An Explorative Study. (June 2016) - Rutegård, M.; Hassmén, N.; Hemmingsson, O.; Haapamäki, M. M.; Matthiessen, P.; Rutegård, J.
Background and Aims: Impaired blood perfusion may be implicated in anastomotic leakage after anterior resection for rectal cancer. We investigated whether high ligation of the inferior mesenteric artery or total mesorectal excision compromises visceral blood flow in the colonic limb and the rectal stump, respectively. Material and Methods: A prospective cohort study was conducted in a university hospital setting. We used Laser Doppler flowmetry to evaluate the impact of level of tie on colonic limb perfusion and the extent of the mesorectal excision on the rectal blood flow. In the rectum, different quadrants were also assessed. The Mann–Whitney U test was used to compare mean blood flow ratios between groups. Results: Some 23 patients were recruited in a convenience sample during a period in 2012–2013. The mean blood flow ratio was not decreased after high tie compared to low tie surgery (1.71 vs 1.19; p = 0.28). Total mesorectal excision reduced the mean blood flow ratio in the rectum, as compared with partial mesorectal excision (0.76 vs 1.28; p = 0.14). This was especially pronounced in the posterior aspect of the rectum (0.66 vs 1.68; p = 0.02). Conclusion: High tie ligation did not seem to decrease colonic limb perfusion, while total mesorectal excision may decrease rectal blood flow. The posterior quadrant of the rectum might be particularly vulnerable to the dissection involved in total mesorectal excision.